Aspergillus spp. invasive external otitis: favourable outcome with a medical approach. (May 2016) - Marchionni, E.; Parize, P.; Lefevre, A.; Vironneau, P.; Bougnoux, M.E.; Poiree, S.; Coignard-Biehler, H.; DeWolf, S.E.; Amazzough, K.; Barchiesi, F.; Jullien, V.; Alanio, A.; et al.
Abstract: Aspergillus spp. invasive external otitis (IEO) is a rare infection. We performed a seven-year, single-centre retrospective study from 2007 to 2014 including all patients with proven Aspergillus spp. IEO. Twelve patients were identified. All patients had a poorly controlled diabetes mellitus and one underwent solid organ transplant. The most frequently isolated species was Aspergillus flavus ( n = 10) and voriconazole was the first-line therapy in all cases, with a median length of treatment of 338.5 days (158–804 days). None of the patients underwent extensive surgery. The clinical outcome was excellent. However, otological sequelae were reported, including hearing impairment ( n = 7) and facial palsy ( n = 3).